Application Design of AI Image Recognition in Power System - Boyan Jia; Zizi Zhang; Jingran Jia; Hongliang Shen; Likun Ding (Advances in Multimedia)
With the continuous development of social economy, more and more attention is paid to the safety of power systems. However, since the power system involves a wide range of areas, how to effectively maintain power safety is extremely important. The AI image recognition technology is introduced to effectively identify the relevant signal lamps, digital instrument panels, switch positions, etc., of power equipment and sort out the specific identification process. Simulation experiments prove that AI image recognition is effective and can support the application of power systems.